Workshop Peningkatan Softskill Pengenalan dan Pemanfaatan Internet Of Things (IOT) Siswa SMK Negeri 1 Air Joman - Nata, Andri; Iqbal, Muhammad; Ramadhani, Andrew (STMIK Royal, 2024)
This workshop aims to enhance the soft skills of vocational high school students through the introduction and utilization of Internet of Things (IoT). Participants will be acquainted with the fundamental concepts of IoT and how this technology can enrich their interpersonal abilities. The workshop focuses on developing communication skills, teamwork, and problem-solving through the implementation of simple IoT projects. Additionally, participants will understand the positive impact of IoT usage in daily life and the industrial sector. Active learning methods, such as group discussions and project simulations, will provide practical experiences that enrich students' understanding of these concepts. Thus, it is anticipated that this workshop will significantly contribute to equipping vocational high school students with relevant soft skills, supporting their readiness to face challenges in the future. Keywords: Internet of Things; arduino; kodular